Analysis Acceptance Of Platform Technology Didimax Berjangka In Pekanbaru Using The UTAUT Method - Rizki Novendra (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2020)
This study discusses the acceptance of PT Didimax's metatrader technology. To carry out the analysis in this study using the UTAUT method. The UTAUT method has four independent variables and two dependent variables. It is through these variables that the level of technology acceptance is explained. The results of this study from 121 respondents showed that the Performance Expectancy variable had a positive and significant impact on behavior intention, the condition t counted 3.184> t table 2015 Sig 0.002 <0.05 and facilitating condition t count 4.224> t table 2015 Sig 0.000 <0.05. also has a positive and significant impact on use behavior